Non-functional parathyroid cyst-diagnostic pitfalls - Polovina, Snezana Petar; Anđelković, Zoran; Micic, Dragan D (Vojnosanitetski pregled, 2015)
Introduction: Parathyroid cysts are relative rare and they may be misdiagnosed with thyroid nodules. Parathyroid cysts are characterized by elevated level of parathyroid hormone (PTH) in cystic fluid. Case report: We reported about middle-aged woman with palpable node in the left thyroid lobe. Ultrasound showed anechoic 40x25 mm lesion in the left thyroid lobe. Fine needle aspiration (FNA) obtained 13 mL colorless, watery cystic fluid. PTH value in cystic fluid was ten fold more in comparison with serum PTH. Serum PTH was slightly elevated, D vitamin was under the reference range, serum calcium and phosphorus were normal as well as thyroid hormones. TgAb and TPOAb were not detected. Radionuclide parathyroid scintigraphy indicated at physiological MIBG distribution. After six months of vitamin D supplementation, serum calcium, phosphorus, vitamin D and PTH were normal. This finding was indicative that was a nonfunctional parathyroid cyst. Conclusion: With this case, we wish to point that thyroid cystic lesions with thin walls, and reverberation in ultrasound, must be observed as a potential parathyroid cyst. These cysts require caution during diagnostic aspiration because of danger of hypercalcemic crises due to FNA, which can be a life-threatening condition. Kezwords: parathyroid cysts, hypercalcemic crises, FNA